Anti-interleukin 4 receptor α antibody for the treatment of Chinese bullous pemphigoid patients with diverse comorbidities and a 1-year follow-up: a monocentric real-world study - Wang, Si-Hang; Shan, Ying; Li, Si-Zhe; Zuo, Ya-Gang (Frontiers in Immunology, 2023)
Background: Bullous pemphigoid (BP) is a common subepidermal bullous disorder that lacks adequate treatment alternatives. Dupilumab, an anti-interleukin (IL) 4 receptor α antibody blocking Th2 molecules IL-4 and 13, has been utilized off-label and shown effective in refractory BP cases. Methods: BP patients with various disease severity and comorbidities were included in this case series. All patients received dupilumab alone or in combination with immunosuppressants in a real-world setting. Complete remission (CR) was defined as the absence of pruritus symptoms and previous BP eruptions, with only hyperpigmentation patches and without newly occurring lesions for at least four weeks. Disease relapse was classified as the appearance of three or more new lesions within one month or at least one large urticarial or eczematous lesion that did not resolve within a week. Findings: Ten individuals were enrolled in this case series. Their pruritus symptoms and BP eruptions improved significantly in nine patients (90%). Seven patients (70%) attained CR, including all mild-to-moderate (100%) and three of six (50%) severe BP cases. At the stage of dupilumab monotherapy, eosinophilia was observed in two severe cases. One patient out of seven (14.3%) relapsed after one year of follow-up following CR. Conclusion: Anti-IL-4 receptor α antibody in treating BP with diverse comorbidities gives further credentials to a prospective randomized study. After one year of follow-up, more impressive efficacy and safety profiles have been observed in patients with mild to moderate disease. Eosinophilia may occur in patients receiving dupilumab monotherapy.